Efektivitas Desinfektan Karbol 4% di Ruang Isolasi Barat ICU RSUD Dr. Moewardi - Pertiwi, Brenda Ervistya; Hudiyono, .; Purwoko, . (Nexus Biomedika, 2013)
Nosocomial infection still becomes a global health problem. An attempt to reduce the risk of nosocomial infections in the ICU (intensive care unit) room of RSUD Dr. Moewardi, 4% carbol has been used routinely in disinfection. This study was to know the effectiveness of 4% carbol disinfectant in West Isolation Room of ICU in RSUD Dr. Moewardi. This study was an analytical observational research with a cross sectional approach. The samples collected from ICU resulted from three groups. Each group was 15 samples, collected from swabbing the floor and the wall (grown on agar), and from the air (grown on blood agar). For each group, 5 samples were taken at 6 am (1 hour before disinfection), at 9 am (2 hours after disinfection) and at 12 pm (5 hours after disinfection). The data were analyzed using Wilcoxon experiment Based on the standard of germs limit on wall, floor (5-10 colony/cm2) and air (â¤200 cfu/m3) at intensive care unit, the result from swabbing the wall and air samples showed that the disinfection was 100% effective. Whereas, the result from swabbing the floor was only 13.33% effective. Between germs number from swabbing the wall collected at 6 am and 9 am represented a significant reduction (p = 0.042). On the other hand, there was no significant reduction of germ number between which were collected at 6 am and 12 pm (p = 0.068) as well as between 9 am and 12 pm (p = 1.000). In addition, there was also no significant reduction of germs number resulting from swabbing the Â floor between collected at 6 am and 9 am (p = 0.080); 6 am and 12 pm (p = 0.080); and 9 am and 12 pm (p = 0.068). Furthermore, the number of air germs between collected at 6 am and 9 am represented a significant reduction (p = 0.043). But, there was no significant reduction between collected at 6 am and 12 pm (p = 0.225), as well as Â at 9 am and 12 pm (p = 0.715). Disinfection with 4% carbol in west isolation room of ICU RSUD Dr. Moewardi showedÂ  effectively controlling germs number on the wall and the air, but it was not effectively controlling on the floor. Keyword: disinfectant, carbon 4%, germs number.